Extraction of Pectin from Orange Peels and Optimization of Process Parameters - Lakshmana Naik, R; Mamatha, J; Bhargavi, J; Nayomi, T; Hema, B (International Journal of Computer Sciences and Engineering, 2019)
The aim of the study was to extract pectin from orange peels. Orange peels are a major commercial source of pectin. Pectin is one of the major important product used in various applications such as food processing industries, pharmaceuticals and its traditional jelling agent for jam and jellies. In the past many researches working on the development of the part of the process technology needed for the extraction of value added products i.e. Pectin from orange peels. Many operating parameters are affecting on the extraction of pectin. It is necessary to understand the effect of various operating parameters on extraction of pectin, in present study effect of Temperature, Solvent used for extraction and time used for extraction where discussed. The effects of pH on extraction of pectin were also discussed; pH is one of the most important crucial parameter which effects on extraction of pectin. When the process conditions were varied, a maximum yield of 52% was obtained, when the temperature at 90°C, pH=1 by using citric acid as a solvent. This study extends the effect of operating parameters an extraction of pectin from orange peels.